Nonpharmaceutical Interventions Remain Essential to Reducing Coronavirus Disease 2019 Burden Even in a Well-Vaccinated Society: A Modeling Study. (9th August 2021) - León, Tomás M; Vargo, Jason; Pan, Erica S; Jain, Seema; Shete, Priya B
Abstract: Vaccination and nonpharmaceutical interventions (NPIs) reduce transmission of severe acute respiratory syndrome coronavirus 2 infection, but their effectiveness depends on coverage and adherence levels. We used scenario modeling to evaluate their effects on cases and deaths averted and herd immunity. NPIs and vaccines worked synergistically in different parts of the pandemic to reduce disease burden.